Tikobulary: vocabulary enrichment the new norm style / Siti Rohayzah Jasman ... [et al.] - Jasman, Siti Rohayzah; Jevanathan, Albert; Hwa, Madeline Liew Szu; Mat Zain, Noor Fadzliana (2020)
The ramification of digital technology during the pandemic era has paved new ways for teachers to adapt and vary teaching strategies to ensure smooth teaching and learning using available resources. Today, social media has become an indispensable part of teenagers' life due to its user-friendly features. Online platform such as Tiktok provides students with a fun learning environment through real-life visualization. The use of Tiktok enables knowledge and information sharing among educators and students which enhances collaborative learning. The innovation of Tikobulary aimed to facilitate matriculation students in acing speaking tasks through a set of vocabulary items commonly used in speaking activities. The ability to speak using correct sentence structure, convey meaning clearly and use appropriate and varied vocabulary in accordance with the social context are the essence of the task. A group of students with low MUET bands (B2-B3) will be recognized and exposed to Tikobulary. The results of the speaking marks before and after the exposure will be compared to identify the effectiveness of Tikobulary in helping the students to improve their speaking skills. It is hoped that with the experience and vocabulary items learned, students will keep their speech going to survive the upcoming MUET speaking test.